A Congenital anomalies and early neonatal mortality: A tertiary hospital study. - Hossam S. Talab; Ahmed Kamal; Khalid Z. Naama (مجلة كلية الطب, 2022)
Background: The prevalence of congenital anomalies at birth is underestimated in developing countries due to the unavailability of perinatal diagnostic tests or accurate medical records.  The prevalence of congenital defects may help to establish a baseline, track changes over time, and uncover etiological clues.